Evaluating antecedents of food waste behavior and reducing college students’ plate waste through an intervention of weighing and displaying the amount of waste with emotional messaging - Zhang, Wenhao (Kansas State University, 2020)
College dining services generate a large amount of food waste, and researchers have explored ways to reduce the waste in these operations. This project included two distinctive studies with the following purposes. First, an online survey was conducted to assess variables affecting self-reported food waste behaviors. Second, a plate waste study was conducted before, during, and after the one-week intervention to evaluate the effectiveness of an intervention of weighing and displaying plate waste amounts while showing factual and emotional food waste related messages. The target population was college students who utilize the on-campus dining facilities, and the study sample included patrons who dined at a large university dining center, located in the Midwest region of the U.S. The study facility was an all-you-care-to-eat dining center where an average of 2,000 diners eat daily. The online survey (Study 1) occurred one week before the plate waste study (Study 2) to minimize the influence of the intervention on psychosocial measurements. Study 1 utilized the modified theory of reasoned action (TRA) including attitudes, subjective norms, behavioral intention, and self-reported food waste behavior with emotions toward food waste as an additional antecedent. The questionnaire was developed based on the TRA and emotions-as-feedback theory, pilot tested, and distributed to all patrons in the facility. Descriptive statistics and structural equation modeling were utilized to analyze the data. Results from 450 college diners’ responses indicated that diners’ intention toward food waste reduction fully mediated the three pathways from attitudes (b=.07, p<.01, CI 90% [.04, .10]), subjective norms (b=.05, p<.05, CI 90% [.01, .10]), and emotions (b=.15, p<.01, CI 90% [.11, .21]) to self-reported food waste behaviors. Diners who reported strong attitudes, subjective norms, and emotions toward food waste also reported higher scores on food waste reduction behaviors through the indirect effects of high intention to reduce food waste. By adding emotions to the model, this study more adequately evaluated the psychological antecedents of food waste behavior, providing additional theoretical supports to existing literature. In Study 2, the amount of edible plate waste was collected at baseline without patrons’ knowledge, followed by a week-long intervention where researchers weighed individual plate waste, live-streamed average and accumulated plate waste amounts, and displayed food waste related messages with an intention to influence diners’ awareness, attitudes, subjective norms, and emotions toward reducing food waste. Post-intervention data was collected after a one-week break. Descriptive statistics, an ANOVA, and cross-tabulation analysis were conducted to analyze the data. The total numbers of trays evaluated before, during, and after the intervention were 2,220, 1,927, and 2,017, respectively. The results indicated that the amount of food waste in grams was significantly reduced during and after the intervention (i.e., before: 47.03±68.15, during: 37.06±68.63, and after: 38.88±68.40, F=12.76, p<.05). Furthermore, more diners left no plate waste during (60.3%) and after the intervention (48.1%) than at the baseline (31.6%, χ2(8)=391.49, p<.05). By implementing the intervention, this study successfully documented improvements in college diners’ plate waste behavior and provided practical implications for university food-service operators for reducing food waste.
Keywords: Food waste; Attitudes; Subjective norms; Emotions; Intention